(untitled) (Communications in Mathematical Research, 2022)
In the study of (partial) difference sets and their generalizations in groups G, the most widely used method is to translate their definition into an equation over group ring Z[G] and to investigate this equation by applying complex representations of G. In this paper, we investigate the existence of (partial) difference sets in a different way. We project the group ring equations in Z[G] to Z[N] where N is a quotient group of G isomorphic to the additive group of a finite field, and then use polynomials over this finite field to derive some existence conditions.